Marine benthic diatoms from the Adriatic Sea (NE Mediterranean): review of investigations and checklist with updated nomenclature - Car, Ana; Kaleli, Aydin (Acta Botanica Croatica, 2025)
Despite more than 30 years of investigations, the knowledge of the composition and spatial distribution of marine benthic diatoms along both coasts of the Adriatic Sea is still limited. The distribution and a checklist of marine benthic diatom taxa in the Mediterranean sub-basin of the Adriatic Sea are presented based on literature data. The nomenclature is brought up to date and synonyms are included. Eight hundred and twenty-two species belonging to 70 families and 163 genera have been reported. The number of pennate species represented was 719. Families with the highest number of genera were: Naviculaceae (8), Bacillariaceae (7), Surirellaceae (6), Fragilariaceae (6). The highest number of taxa belonged to the Naviculaceae (95) and Bacillariaceae (88). The most numerous genera were Mastogloia (65 taxa), Navicula (62), Nitzschia (53), Amphora (52), Diploneis (43), Cocconeis (37), Halamphora (24), Achnanthes (22), Licmophora (22), Tryblionella (19), Fallacia (15), Surirella (14), Grammatophora (13), and Lyrella (12). This study focused on the areas of investigation according to the literature reviewed and showed that many areas have to be investigated. Nevertheless, this first comprehensive checklist of marine benthic diatoms in the Adriatic Sea, updated with recent literature, is a valuable tool. However, it is important that this update has been progressive over time. Incorporating data on diatom taxa will improve the overall diversity of microalgae and our knowledge of the ecology of coastal ecosystems.